My Word is My Bond - Moore, Roger, 1927- and Owen, Gareth, 1973- (London Michael O'Mara Books, 2008)
A memoir by the actor best known for his portrayal of James Bond discusses how his career has been shaped by his iconic roles, his devotion to charity work, and his relationships with famous figures and fellow celebrities
Include Color Illustration and Index
Keywords: Motion picture actors and actresses -- Great Britain -- Moore, Roger, 1927-